2016
DOI: 10.1179/1743284715y.0000000128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sn, Ca additions on thermal conductivity of Mg matrix alloys

Abstract: In the present work, the effects of Sn, Ca additions on thermal conductivity were investigated in as cast Mg–Sn–Ca alloys. The measured values of thermal conductivity of Mg–3Sn– xCa alloys obviously increased from 85.6 to 126.3 W m− 1 K− 1 with the increasing Ca from 0 to 1.5 wt-, and then decreased to 98.3 W m− 1 K− 1 with the 2.5 wt- Ca. In addition, the thermal conductivity of the Mg–Sn–Ca (Sn/Ca atomic ratio of 1) alloys decreased slightly from 154.2 to 132.1 W m− 1 K− 1 with the increasing Sn, Ca. Meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…According to the above microstructure and Table 3, it can be considered that the increased lattice distortion, destruction of lattice periodicity and number of Mg 7 Zn 3 particles (scattering centers), with addition of Nd content mainly account for the thermal conductivity of designed Mg alloys decreases with Nd content. The variation trend of thermal conductivity of the Mg alloys with alloy element content is in agreement with previous investigations [8,9,17,19,21,30].…”
Section: Effect Of Nd Content On the Thermal Conductivitysupporting
confidence: 92%
See 1 more Smart Citation
“…According to the above microstructure and Table 3, it can be considered that the increased lattice distortion, destruction of lattice periodicity and number of Mg 7 Zn 3 particles (scattering centers), with addition of Nd content mainly account for the thermal conductivity of designed Mg alloys decreases with Nd content. The variation trend of thermal conductivity of the Mg alloys with alloy element content is in agreement with previous investigations [8,9,17,19,21,30].…”
Section: Effect Of Nd Content On the Thermal Conductivitysupporting
confidence: 92%
“…Since the different elements have the different effects on the mechanical properties [10][11][12][13][14][15] and thermal performance [2][3][4][16][17][18][19][20][21][22] of the Mg alloys, the alloying element type and concentration of the Mg alloys developed for the applications of heat dissipation should be carefully chosen in order to get a good balance between the thermal and mechanical properties. So far, most studies [2,3,9,16,17,19,20] have focused on the thermal conductivity of the Mg alloys without consideration from the angle of good combination of mechanical and thermal properties, which is undesirable for the applications of heat dissipation. It was reported that the cast Mg-Zn-Mn alloy exhibits the heat conductivity of 125 W/(m•K) [22] which is about twice as high as that of AZ91 and AM60, and the extruded Mg-Mn-Zn system alloys with a low content of Nd exhibit good strength [23].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys are the lightest metal structures and have become widely used in the aerospace, automotive, electronic, instrumentation, and communication fields, among others [1,2]. However, their low strength and ductility have become bottlenecks, limiting their industrial application and reducing the possibility of their replacement of aluminium alloys [3,4]. In particular, rare-earth (RE) magnesium alloys have recently triggered extensive research because of their high strength, corrosion resistance, heat resistance, and excellent casting and mechanical properties [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Mg-Sn based alloys are noteworthy materials for application at elevated temperatures [6,7,8,9]. In addition, Ca element forms a thermally stable CaMgSn phase (Sn/Ca weight ratio: 3/1~3.5/1) with Sn and Mg in the Mg-Sn alloy, which further improves the elevated temperature properties of the alloy [10,11,12,13]. However, the micromechanical properties and corrosion behavior of Mg-Sn alloys are rarely reported.…”
Section: Introductionmentioning
confidence: 99%